1, 2, 3-Dithiazoles – new reversible melanin synthesis inhibitors: a chemical genomics study. Issue 5 (13th May 2015) - Charalambous, Anna; Koyioni, Maria; Antoniades, Ioanna; Pegeioti, Despoina; Eleftheriou, Iro; Michaelidou, Sophia S.; Amelichev, Stanislav A.; Konstantinova, Lidia S.; Rakitin, Oleg A.; Koutentis, Panayiotis A.; Skourides, Paris A.
<x xml:space="preserve">Abstract</x> 1, 2, 3-Dithiazolimines show potent and reversible inhibition of melanin synthesis in Xenopus laevis embryos.